Organizational Justice and Whistleblowing: An Experimental Test - Abraham Kurniawan; Intiyas Utami; David Ade Chandra Ashedica Pesudo (Institute of Research and Community Outreach - Petra Christian University, 2019)
Whistleblowing has become an important issue at the organization recently because it enables individuals to disclose any regulation’s errors in the organization to their superior. Whistleblowing could be caused by several factors, one of which is organizational justice. The organizational justice consists of distributive justice and procedural justice. The objective of this research is to examine the causality of organizational justice to whistleblowing intention. This research was conducted with 2x2 between-subjects experimental design. The results show that when an individual is faced with fair distributive justice or fair procedural justice, they have the tendency to whistle the fraud. When an individual is faced with unfair procedural justice and fair distributive justice, they also tendto whistle the fraud.